REINSTATING FOR ENTREPRENEUR TERMINOLOGY IN MANAGEMENT, AN ALTERNATIVE OF CRITICAL DISCOURSE - Oscarius Yudhi Ari Wijaya (LPPM Press STIE Indragiri Rengat, 2022)
Academic scientific culture has encouraged the birth of many new ideas, both in the form of new theoretical conceptions and modeling of a research, including several new ideas. which gave birth to new terms in a scientific field, including the field of management, including the term